PERAN MODERASI KUALITAS AUDIT PADA PENGARUH KONEKSI POLITIK TERHADAP NILAI PERUSAHAAN - Liyanto, Stanesie; Daromes, Fransiskus E.; Jantong, Alfonsus (School of Accountancy, University of Agung Podomoro, 2022)
This study aims to examine the moderating role of audit quality on the effect of politicalconnections on firm value. The population used in this study are manufacturing companies listed onthe Indonesia Stock Exchange with a research period of 2016-2019. The number of samples is 108companies each year. Data analysis used moderated regression test. The results of the study prove thatpolitical connections have a positive and significant influence on firm value, however, audit qualitycannot moderate the relationship between political relations and firm value.